2010
DOI: 10.2202/1548-923x.2045
|View full text |Cite
|
Sign up to set email alerts
|

Cognitions and Clinical Performance: A Comparison of High and Low Performing Baccalaureate Nursing Students

Abstract: Studies to date have employed a variety of methods to elucidate the cognitive processes that underlie nursing actions in clinical situations. Most studies relied on clinical case scenarios rather than actual patient care situations, and did not supplement cognitive measures with quantitative measures of performance or physiologic outcomes of care. The present study employed a quasi-experimental design to describe and compare the verbal report data of baccalaureate nursing students who were assigned to high and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In problem-solving, understanding the nature of problems makes it easy to achieve the desired results (Bandura, 1986). Cognitive processing ability increases the level of work capacity and consequences (Truxillo, Seitz & Bauer, 2008) and the ability to complete a task (Chen, Casper, & Cortina, 2001;Cormier, Pickett-Hauber & Whyte, 2010). Thus, self-efficacy evolves in the positive direction (Chemers, Hu, & Garcia, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In problem-solving, understanding the nature of problems makes it easy to achieve the desired results (Bandura, 1986). Cognitive processing ability increases the level of work capacity and consequences (Truxillo, Seitz & Bauer, 2008) and the ability to complete a task (Chen, Casper, & Cortina, 2001;Cormier, Pickett-Hauber & Whyte, 2010). Thus, self-efficacy evolves in the positive direction (Chemers, Hu, & Garcia, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports provide a modicum of construct validity for the use of simulators in health care. For example, Cormier et al 22 used a high-fidelity medical simulation to distinguish between lowand high-performing student nurses based on their ability to prioritise patient care more effectively. Similarly, Schijven and Jakimowicz 23 highlighted the potential of simulations to differentiate expert from novice surgical providers.…”
Section: Stage 1: Capturing Expert Performancementioning
confidence: 99%
“…The degree to which the simulation recreates the demands of the actual task or situation will provide high (or low) levels of both internal and external validity. For instance Cormier, Hauber, and Whyte (2010) found that performance differences among novices materialized when making complex assessments regarding a deteriorating patient's status rather than while completing a host of routine nursing tasks. In addition, an expert performer will consistently perform well on the majority of tasks within a domain.…”
Section: E60)mentioning
confidence: 99%